Globalization for South Korea’s Cultural Industry: The Future of K-Pop in The Untact Era - Gloria Theodora Kardinal (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2021)
This study will discuss the role of globalization in the development of Culture Technology in the South Korean entertainment industry, particularly as a strategy and vision presented by SM Entertainment. Various new innovations for the entertainment world in the future, especially in the face of the Covid-19 pandemic situation or the untact era, ranging from online concerts to the use of social media as a new business model. The main purpose of this article is to understand and describe the use of technology in the South Korean entertainment industry. The theory used in this research is globalization theories, with descriptive qualitative research methods. Data mining was carried out by observation using secondary data that supported this research, from books, online reporting, presentations and presentations, as well as previous research journals. The author concludes that technological advances have had a significant impact on the entertainment industry and the spread of popular culture, K-Pop, in an untact era to entertainment companies such as SM Entertainment, which continues to innovate in technology that is leading the industry to stay connected with audiences globally and become opportunities for future advancement.